2012
DOI: 10.1371/journal.pone.0035708
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin Treatment of Cachectic Patients with Chronic Obstructive Pulmonary Disease: A Multicenter, Randomized, Double-Blind, Placebo-Controlled Trial

Abstract: BackgroundPulmonary cachexia is common in advanced chronic obstructive pulmonary disease (COPD), culminating in exercise intolerance and a poor prognosis. Ghrelin is a novel growth hormone (GH)-releasing peptide with GH-independent effects. The efficacy and safety of adding ghrelin to pulmonary rehabilitation (PR) in cachectic COPD patients were investigated.Methodology/Principal FindingsIn a multicenter, randomized, double-blind, placebo-controlled trial, 33 cachectic COPD patients were randomly assigned PR w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
88
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(92 citation statements)
references
References 36 publications
1
88
0
3
Order By: Relevance
“…However, the morphological characteristics and thorough distribution of ghrelin cells in the gastrointestinal tract has not been defined. Ghrelin is also produced in small amounts by other organs like heart, lung, lymphatic tissue, kidney, adrenal glands, thyroid gland, pancreas, gonads, some neoplastic tissues and cancer-cell lines [15][16][17]. Ghrelin-immunoreactive neurons are present in few regions of the brain like the arcuate and the ventromedial nucleus of the hypothalamus, cerebellum and brainstem [12,[18][19][20].…”
Section: Observationmentioning
confidence: 99%
“…However, the morphological characteristics and thorough distribution of ghrelin cells in the gastrointestinal tract has not been defined. Ghrelin is also produced in small amounts by other organs like heart, lung, lymphatic tissue, kidney, adrenal glands, thyroid gland, pancreas, gonads, some neoplastic tissues and cancer-cell lines [15][16][17]. Ghrelin-immunoreactive neurons are present in few regions of the brain like the arcuate and the ventromedial nucleus of the hypothalamus, cerebellum and brainstem [12,[18][19][20].…”
Section: Observationmentioning
confidence: 99%
“…In our study, we found a higher ghrelin concentration in patients with frequent exacerbations, but the difference was not significant. There have been attempts to treat patients with COPD and cachexia with ghrelin, 41,42 and the results seem quite encouraging. The anti-inflammatory effect of ghrelin was also the subject of studies in the experimental model of colitis, 43 hepatic disorders, 44 sepsis, 45 and rheumatoid arthritis.…”
mentioning
confidence: 99%
“…104,105 Among the first applications of ghrelin in human chronic illness were studies in congestive heart failure (CHF) 106 and chronic obstructive pulmonary disease (COPD). 107,108 In the field of surgery, ghrelin comprehensively improves the patients' general conditions and quality of life via its pleiotropic physiological functions. This characteristic is unique and different from the existing drugs.…”
Section: Clinical Applications Of Ghrelin and Ghrelin Antagonistmentioning
confidence: 99%